Masking of fetal supraventricular tachycardia by electronic monitoring artefact. - Post, W D (1984)
In a fetus of 42 weeks' gestation electronic monitoring demonstrated a heart rate of 120 beats/min that lacked the normal variability. Auscultation with a fetoscope revealed the true rate to be 240 beats/min. When used in the external Doppler mode the fetal monitor had a 250-ms refractory period after the recognition of a fetal cardiac event. This precluded recognition of the next beat and produced the artefactual halving of the heart rate. With the increasing reliance upon electronic fetal monitoring, those practising obstetrics should be aware of the possibility of artefacts and ensure that they can recognize truly representative information about the fetus.